Proton‐Transfer Dynamics of Photoacidic Merocyanines in Aqueous Solution. Issue 35 (1st June 2021) - Kaiser, Christoph; Halbritter, Thomas; Heckel, Alexander; Wachtveitl, Josef
Abstract: Photoacids attract increasing scientific attention, as they are valuable tools to spatiotemporally control proton‐release reactions and pH values of solutions. We present the first time‐resolved spectroscopic study of the excited state and proton‐release dynamics of prominent merocyanine representatives. Femtosecond transient absorption measurements of a pyridine merocyanine with two distinct protonation sites revealed dissimilar proton‐release mechanisms: one site acts as a photoacid generator as its pKa value is modulated in the ground state after photoisomerization, while the other functions as an excited state photoacid which releases its proton within 1.1 ps. With a pKa drop of 8.7 units to −5.5 upon excitation, the latter phenolic site is regarded a super‐photoacid. The 6‐nitro derivative exhibits only a phenolic site with similar, yet slightly less photoacidic characteristics and both compounds transfer their proton to methanol and ethanol. In contrast, for the related 6, 8‐dinitro compound an intramolecular proton transfer to the ortho ‐nitro group is suggested that is involved in a rapid relaxation into the ground state. Abstract : Transient absorption studies of protonated pyridine‐ and nitro‐merocyanines reveal a pH‐gated photoacidic behaviour. The O‐protic site shows an ultrafast excited state super‐photoacid reactivity at low pH values that is even capable of proton transfer to alcoholic solvents. Remarkably, the pyridine compound exhibits an additional N‐protic site which functions as photoacid generator at pH 5.5 due to its lowered ground state pKa value after photoisomerization to the ring‐closed spiropyran structure.